1990
DOI: 10.1080/09540129008257740
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural change in injecting drug users: Evaluation of an HIV/AIDS education programme

Abstract: The results obtained from the training and follow-up of 189 IDUs who participated in a programme consisting of an audiovisual presentation, pre-/post-testing and individual counselling are presented. Syringe sharing decreased from 35% at initial contact to 12% after 6 months. Sexual behaviour proved more resistant to change. However, condom use in at-risk situations increased from 49% to 70%. IDUs under continuous methadone treatment were less likely to engage high risk drug injecting practices than the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…duction in needle sharing. 5 The US General Accounting Office 48 reported on a study 50 that found that 9% of the injection drug users in methadone maintenance shared needles, whereas 48% of the injection drug users not in treatment shared needles, indicating an 81% reduction in needle sharing. We assumed that injection drug users in methadone maintenance inject 20% as often as injection drug users not in treatment (an 80% reduction in frequency) and share 30% as often as injection drug users not in treatment (a 70% reduction in sharing), leading to a 94% reduction in risky injections among injection drug users in methadone maintenance (20% × 30% = 6% as many risky injections).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…duction in needle sharing. 5 The US General Accounting Office 48 reported on a study 50 that found that 9% of the injection drug users in methadone maintenance shared needles, whereas 48% of the injection drug users not in treatment shared needles, indicating an 81% reduction in needle sharing. We assumed that injection drug users in methadone maintenance inject 20% as often as injection drug users not in treatment (an 80% reduction in frequency) and share 30% as often as injection drug users not in treatment (a 70% reduction in sharing), leading to a 94% reduction in risky injections among injection drug users in methadone maintenance (20% × 30% = 6% as many risky injections).…”
Section: Methodsmentioning
confidence: 99%
“…We assumed that injection drug users not in treatment inject 200 times per year in the low-prevalence community and 225 times per year in the high-prevalence community [38][39][40][41][42][43][44] and that they share needles 20% of the time, 5,[40][41][42][43][45][46][47] leading to 40 and 45 risky injections per year, respectively, in the 2 communities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants who adhered continuously to methadone treatment were less likely to share needles (18%) than were those who interrupted treatment (39%); after 1 year, the rate of syat North Dakota State University on June 25, 2015 http://cid.oxfordjournals.org/ Downloaded from ringe or needle sharing decreased from 35% to 12% [48]. With regard to HIV transmission, HIV seroconversion was ∼3.5% in IDUs who remained adherent to methadone maintenance treatment versus 22% in untreated patients after 1 year [36].…”
Section: Resultsmentioning
confidence: 86%
“…Donoghoe et al, 1989;Mulleady et al, 1990) very little research has been published to date on attempts to change the sexual behaviour of this client group. In Italy, following educational and counselling interventions with drug users, both Martin et al (1990) and Nicolisi et al (1991) concluded that sexual behaviour was more difficult to change than drug-using behaviour. In America Schilling et al (1 99 1) undertook a skills-building intervention for female methodone patients which provided only modest moderation of sexual risk behaviour.…”
Section: Introductionmentioning
confidence: 97%